Formation of management mechanism for small businesses financial security - Калмиков, Олег Валентинович (Technology audit and production reserves, 2015)
The state of problem elaboration concerning the formation of the mechanism of small businesses financial security management (further SB) is analyzed; the concept of «financial SB security» is defined. The financial security of a small business is defined as a financial position which is characterized by balance and quality of the financial tools set, instruments used by small business, resistance to internal and external threats, the ability of small business financial policy for ensuring the implementation of its financial interests, mission and objectives with sufficient financial resources and to guarantee its efficient and sustainable development. Its goals and objectives are formulated; methods of detection and assessment of threats to SB financial security and its criteria are defined; algorithm of the management of SB financial security functioning and logical-structural pattern of conducting structural analysis of SB financial security are worked out. The need to use strategic analysis in the process of financial security management of business is caused by such reasons as: the implementation of the effective management in relation to financial security; development of a strategy for ensuring the financial security of the company; identification of possible risks and threats to financial security at business level; determination of the factors that affect the level of business financial security; identification of internal resources and capabilities for ensuring financial security, etc.